1994
DOI: 10.1080/00071669408417717
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological and shelf life assessment of chilled eviscerated whole chicken broilers in Saudi Arabia

Abstract: 1. The microbiological quality and shelf life of chicken carcasses marketed in Riyadh, Saudi Arabia were assessed. 2. The mean initial microbial counts (log10 count/cm2) were 4.67, 4.14, 2.21, 2.78 and 2.96 for total aerobes, psychrotrophs, coliforms, Staphylococcus aureus and yeasts and moulds, respectively; these counts suggest a moderate level of contamination during processing. 3. Yeasts and moulds were present in relatively large numbers and constituted a considerable portion of the spoilage flora. 4. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Waldroup (1996) reported that S. aureus counts in poultry meat varied between 53 and 45 log 10 cfu/g. Á lvarez-Astorga et al (2002) determined that average S. aureus count for broiler leg meats was 2.47 log cfu/g, and Al-Mohizea et al (1994) found that S. aureus count for broiler meats was 2.78 log 10 cfu/cm 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Waldroup (1996) reported that S. aureus counts in poultry meat varied between 53 and 45 log 10 cfu/g. Á lvarez-Astorga et al (2002) determined that average S. aureus count for broiler leg meats was 2.47 log cfu/g, and Al-Mohizea et al (1994) found that S. aureus count for broiler meats was 2.78 log 10 cfu/cm 2 .…”
Section: Resultsmentioning
confidence: 99%
“…In one of these studies, Gallo, Schmitt and Schmidt-Lorenz (1988) observed that a yeast population of 10 2 CFU/ cm 2 on the skin of freshly slaughtered chicken increased about 2.5 log CFU/cm 2 during storage at 4°C for 8 days. Populations of 3.1 log CFU/g (Geornaras, Dykes & von Holy, 1994) and 2.2-4.1 log CFU/cm 2 (Al-Mohizea, Mashhadi, Fawwal, & Al-Shalhat, 1994) were detected on fresh chicken carcasses. Yeast populations less than 1 log CFU/g on chicken gizzards increased to 6 log CFU/g during storage at 3 ± 1°C for 16 days (Charoenpong & Chen, 1979).…”
Section: Microbiological Analysesmentioning
confidence: 98%
“…While in case of without skin broiler meat tissue these values were log 7.368 and log 7.416 respectively. Mohizea et al (1994) observed the initial total viable count (log 10 cfu/cm 2 ) which ranged from log 3.8 to 5.5 with a mean of log 4.67. In the present research work however it was found relatively higher in fresh broiler meat tissue.…”
Section: Resultsmentioning
confidence: 99%